ERROR ANALYSIS ON USING LEXICO GRAMMATICAL FEATURES IN DESCRIPTIVE TEXT OF GRADE XI STUDENTS’ - Asima Rohana Sinaga; Triputri Harefa; Firinta Togatorop (Dharmas Education Journal (DE_Journal), 2024)
Writing is a result of the process in inventing a topic and its idea together with words to express the topic and idea in short text. This thesis investigates students' errors in using lexico grammatical features in descriptive text writing. The research follows various theories and uses a qualitative researcher to analyze data from 31 grade XI students in class XI RPL 2. The data was analyzed into four types of errors: omission, addition, misformation, and misordering errors. The analysis revealed that students often made lexical errors and grammatical errors, such as omission, addition, misformation, and misordering letter errors. There were also two causes of errors: interlingual cause and intralingual cause. The conclusion is that grade XI students at SMK Negeri 3 Pematangsiantar often make errors in writing descriptive text due to lexico grammatical errors. To address this issue, the students are suggested to learn more about tenses, make them more attractive and active, and practice them in their daily conversations. This will help them become familiar with using tenses and improve their writing skills.